Evaluating the efficiency of the Dental Teacher system as a digital preclinical teaching tool. (23rd May 2018) - Nagy, Z. A.; Simon, B.; Tóth, Z.; Vág, J.
Abstract: Aim: To investigate the use of a preparation evaluation system for enhancing the learning and performance of undergraduate dental students when cutting preparations. Materials and Methods: Two groups of eighteen students each were randomly chosen from the fourth year of the dental programme. The task chosen for this study was to make a cavity in preparation for a mesio‐occlusal ceramic onlay in a plastic tooth. The dimensions of the cavity were defined, and 2 burs of known size were used for preparation. For assessment, each tooth preparation was scanned with a digital scanner and analysed using the Dental Teacher software. In the control group, a second corrective preparation was made following the supervisor's instructions. In the test group, the second preparation was made based on Dental Teacher analysis. The final cavities were all scanned and assessed by Dental Teacher comparing the similarity of students' onlay cavity preparations to the ideal preparation. All data were recorded and analysed by the software, including cavity depth and width in the occlusal and proximal box, the extent of mesiobuccal cusp reduction and shoulder width around the mesiobuccal cusp. Finally, the data were statistically evaluated using a Wilcoxon matched pairs test and a Mann‐Whitney U test. Results: Three of the 6 cavity dimension parameters improved significantly in the test group whilst no improvement was found in the control group. A positive correlation was found between the improvement and the deviation measured for the first preparations, and it was stronger in the test group than in the control group. Conclusions: The use of Dental Teacher helped students to learn the preparation technique for onlay restorations more efficiently and seems to be a promising and useful method to facilitate their individual performance. Student feedback showed a great demand for digital aids in education.